HUBUNGAN DURASI MENSTRUASI, AKTIFITAS FISIK, DAN KUALITAS TIDUR DENGAN KEJADIAN DISMINORHEA PADA REMAJA PUTRI - Shelly Sagita; Fika Minata; Rizki Amalia; Sendy Pratiwi Rahmadhani (Jurnal Kesehatan dan Pembangunan, 2023)
Adolescence is a transitional period marked by physical, emotional and psychological changes. Adolescence, namely the period between 10-19 years, is a period of maturation of the human reproductive organs which is often referred to as puberty. It is during puberty that there are problems that are often faced by adolescents during menstruation. Based on data from the World Health Organization in 2013, it was found that there were 1,769,425 teenage girls aged 10-19 years who experienced primary dysmenorrhoea of ​​10-15%, there was an increase in 2017 of 54.89% and in 2018 the incidence of dysmenorrhoea in the world was very high. where the average incidence of dysmenorrhea reaches 16.8 - 81%. This study aims to determine the relationship between physical activity, menstrual duration and sleep quality with the incidence of dysmenorrhea in young women at SMP Negeri 4 Indralaya Utara, Ogan Ilir Regency in 2022. The method in this study used a cross-sectional study with a population of 60 respondents and a sample of 60 respondents using the technique total sampling. Data analysis used the chi square statistical test with p value ≤ α value (0.05). The results of this study were 48 respondents with normal menstrual duration who experienced dysmenorrhea as many as 40 people (83.3%) with p value = 0.000, of 42 respondents with moderate activity who experienced dysmenorrhea as many as 28 people (66.7%) p value = 0.03, meanwhile, out of 26 respondents with good sleep quality, 12 people (46.2%) experienced dysmenorrhoea, p value = 0.000. Midwives are expected to further improve services and education for young women regarding reproductive health in adolescents, especially dysmenorrhea.